Solid-cystic pseudo papillary tumor of the pancreas discovered during presentation of acute appendicitis - Kotti Ahmed; Triki Wissem; Abbassi Imed; Ayed Karim; Ganzoui Imen; Bouchoucha Sami (Elsevier, 2021)
Objective: to present a rare case of pancreatic pseudo-papillary and solid tumor in children and to make a review of the literature. Background: Solid-pseudo-papillary tumor of the pancreas (TPPS) is infrequently case of neoplasm in children. It is low-grade malignant potential. Case report: A 15-year-old boy with a pancreatic solid pseudo papillary tumor (TPPS) is reported, discovered after acute appendicitis. ultrasound and Contrast enhanced computerized tomography (CECT) abdomen revealed acute appendicitis and pancreatic mass centered on the distal pancreas. In the first step, appendectomy was done and the exploration was completed. After few months, distal pancreatectomy with spleen preservation was done. The histopathologic report was a pancreatic solid pseudo papillary tumor without malignant cells. Clinical evolution has been satisfactory without recurrence of the tumor till 10 months of follow-up. Conclusions: the most common clinical presentation is abdominal mass. The treatment is surgical and Distal pancreatectomy offers an excellent prognosis.